2009
DOI: 10.1203/pdr.0b013e3181991c67
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JNK Enhances TGF-β1-Activated Smad2 Signaling in Mouse Embryonic Lung

Abstract: The Smad2/3 pathway plays a key role in mediating TGF-␤1 inhibition of branching morphogenesis and induction of connective tissue growth factor (CTGF) expression in embryonic lungs. Because a number of cell-specific interactions have been described between TGF-␤1-driven Smad signaling and the c-Jun N-terminal kinase (JNK) pathway, we have investigated the effects of JNK inhibition on TGF-␤1 activation of Smad2, inhibition of branching, induction of CTGF expression, and apoptosis in mouse embryonic lung explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Second, the use of different strains of mice, at variable gestational ages, and different doses of JNK inhibitors can lead to significantly different results. To illustrate, in contrast to our findings, the JNK inhibitor SP600125 at a dose of 10 μM, used in lung explants obtained from CD1 mice at embryonic day 12.5, induced endogenous CTGF expression, TGFβ1-induced CTGF expression, increased DNA fragmentation and cleaved caspase 3 [19]. Adult JNK1 null mutant mice have been reported to have increased susceptibility to hyperoxia [6].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Second, the use of different strains of mice, at variable gestational ages, and different doses of JNK inhibitors can lead to significantly different results. To illustrate, in contrast to our findings, the JNK inhibitor SP600125 at a dose of 10 μM, used in lung explants obtained from CD1 mice at embryonic day 12.5, induced endogenous CTGF expression, TGFβ1-induced CTGF expression, increased DNA fragmentation and cleaved caspase 3 [19]. Adult JNK1 null mutant mice have been reported to have increased susceptibility to hyperoxia [6].…”
Section: Discussionmentioning
confidence: 82%
“…Firstly, the JNK pathway has been implicated in TGF-β1 signaling in lung cells [19,24,26-29], specifically CTGF [19,26,28] and cell death [19,27] as well as myofibroblast transformation [24]. Secondly, hyperoxia has been shown to upregulate TGF-β1 in premature rat lungs [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ERK has also been demonstrated to have the ability to phosphorylate serines and threonines in the linker region of SMAD2/3, and mutation of specific ERK-target serine and threonine residues of SMAD3 results in potentiated SMAD3 signaling, suggesting that ERK can inhibit SMAD3 signaling via this mechanism [38]. Previous reports also demonstrate the ability of JNK activation to antagonize TGFβ signaling and TGFβ-mediated SMAD activation [3941], in support of our findings that pharmacological inhibition of JNK signaling results in increased fibroblast activation.…”
Section: Discussionmentioning
confidence: 99%
“…The cell-specific differences in crosstalk between MAPK and Smad pathways are also evident with the JNK pathway. Where active JNK enhances or maintains TGFβ-mediated expression in fibroblasts(41) and mesangial cells(42) through phosphorylation of C-terminal Smad2, inhibiting JNK activity in embryonic lung explants increases both endogenous and TGFβ-induced Smad phosphorylation (45) suggesting that active JNK antagonizes TGFβ-induced pSmad2. In yet another study, TGFβ-activated JNK was shown to only phosphorylate Smad3 outside the C-terminal SXS motif in Mv1Lu cells (46).…”
Section: Discussionmentioning
confidence: 99%